Baseline serum albumin and its dynamic change is associated with type 2 diabetes risk: A large cohort study in China. Issue 5 (20th February 2020) - Hu, Fulan; Lou, Yanmei; Shi, Jing; Cao, Liming; Wang, Changyi; Ma, Jianping; Peng, Xiaolin; Xu, Shan; Chen, Hongen; Zhao, Dan; Zhao, Yang; Guo, Chunmei; et al.
Abstract: Background: The study aimed to investigate the associations of baseline serum albumin level and its dynamic change with type 2 diabetes mellitus (T2DM) risk in a large Chinese cohort study. Methods: This cohort study included 30 442 adults without T2DM at first entry, who completed at least one follow‐up of annual examinations between 2009 and 2016. Serum albumin level was measured at baseline and at every annual check‐up. The dynamic change in serum albumin level (∆ALB) was calculated by subtracting serum albumin level at baseline from that at the last follow‐up. Hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated with Cox regression models. Results: During 7 years of follow‐up, we identified 1634 T2DM events. From the lowest to the highest quartile of serum albumin level, adjusted HRs (95% CI) were 1.00 (reference), 0.96 (0.94, 1.01), 0.98 (0.95, 1.02) and 0.88 (0.85, 0.98), respectively. As compared with stable change in serum albumin (−0.2 ≤ ∆ALB <1.0 g/L), the risk of T2DM increased for ∆ALB < −2.0 g/L (HR 1.44, 95% CI 1.24‐1.68) and decreased for ∆ALB ≥3.0 g/L (0.81, 0.68‐0.97) after adjusting for potential confounding factors. Restricted cubic splines showed a linear dose‐response association between baseline serum albumin level and T2DM risk ( P nonlinearity 0.715) and a nonlinear dose‐response association between ∆ALB and T2DM risk ( P nonlinearity 0.011). Conclusions: Baseline serum albumin level appears to be inversely associated with T2DM risk. Adults with reduced serum albumin level could be early identified for diabetes risk in clinical practice.